Unit cost of healthcare services at 200-bed public hospitals in Myanmar: what plays an important role of hospital budgeting? - Thet Mon Than; Yu Mon Saw; Moe Khaing; Ei Mon Win; Su Myat Cho; Tetsuyoshi Kariya; Eiko Yamamoto; Nobuyuki Hamajima (BMC, 2017)
Abstract Background Cost information is important for efficient allocation of healthcare expenditure, estimating future budget allocation, and setting user fees to start new financing systems. Myanmar is in political transition, and trying to achieve universal health coverage by 2030. This study assessed the unit cost of healthcare services at two public hospitals in the country from the provider perspective. The study also analyzed the cost structure of the hospitals to allocate and manage the budgets appropriately. Methods A hospital-based cross-sectional study was conducted at 200-bed Magway Teaching Hospital (MTH) and Pyinmanar General Hospital (PMN GH), in Myanmar, for the financial year 2015-2016. The step-down costing method was applied to calculate unit cost per inpatient day and per outpatient visit. The costs were calculated by using Microsoft Excel 2010. Results The unit costs per inpatient day varied largely from unit to unit in both hospitals. At PMN GH, unit cost per inpatient day was 28,374 Kyats (27.60 USD) for pediatric unit and 1,961,806 Kyats (1908.37 USD) for ear, nose, and throat unit. At MTH, the unit costs per inpatient day were 19,704 Kyats (19.17 USD) for medicine unit and 168,835 Kyats (164.24 USD) for eye unit. The unit cost of outpatient visit was 14,882 Kyats (14.48 USD) at PMN GH, while 23,059 Kyats (22.43 USD) at MTH. Regarding cost structure, medicines and medical supplies was the largest component at MTH, and the equipment was the largest component at PMN GH. The surgery unit of MTH and the eye unit of PMN GH consumed most of the total cost of the hospitals. Conclusion The unit costs were influenced by the utilization of hospital services by the patients, the efficiency of available resources, type of medical services provided, and medical practice of the physicians. The cost structures variation was also found between MTH and PMN GH. The findings provided the basic information regarding the healthcare cost of public hospitals which can apply the efficient utilization of the available resources.